Mattel, Inc.: Global Manufacturing Principles (GMP) – A Life-Cycle Analysis of a Company-Based Code of Conduct in the Toy Industry - Sethi, S. Prakash 1934-; Veral, Emre A.; Shapiro, H. Jack; Emelianova, Olga (2011)
Over the last 20+ years, multinational corporations (MNCs) have been confronted with accusations of abuse of market power and unfair and unethical business conduct especially as it relates to their overseas operations and supply chain management. These accusations include, among others, worker exploitation in terms of unfairly low wages, excessive work hours, and unsafe work environment; pollution and contamination of air, ground water and land resources; and, undermining the ability of natural government to protect the well-being of their citizens. MNCs have responded to these accusations by creating voluntary codes of conduct which commit them to specific standards for addressing these issues. These codes are created at both the industry-wide and the individual company level. Unfortunately, these codes have generated little credibility and public trust because their compliance claims cannot be independently verified, and they lack transparency and full public disclosure. In this article, we present a case study of the voluntary code of conduct by Mattel, Inc., the world’s largest toy company. The code, called the Global Manufacturing Principles (GMP), confronts the general criticism leveled against voluntary codes of conduct by (a) creating detailed standards of compliance, (b) independent external monitoring of the company’s compliance with its code of conduct, and (c) making full, and uncensored public disclosure of the audit findings and company’s response in terms of remedial action. We present a detailed account of how Mattel’s voluntary code of conduct was created, implemented, and ultimately abandoned over 9 years. We provide an evaluative analysis of the company’s GMP compliance throughout its life span, which suggests a bell-shaped curve, where early top management commitments were met with pockets of resistance from operational groups, who were concerned about balancing GMP compliance efforts with traditional performance criteria. The early stage response from Mattel’s top management was quick and supported with the requisite resources. As a result, the compliance process accelerated, becoming increasingly more robust and effective. The success of code compliance and increased transparency in public disclosure energized field managers with a sense of professional satisfaction and publicly recognized accomplishments. The decline in GMP compliance was equally steep. When all the easily attainable targets had been reached at the company-operated plants, addressing vendor plants’ compliance presented a new set of challenges, which taxed corporate resources and management commitment. It would seem that value-based and ethics-oriented considerations, i.e., doing the right thing for the right reason, were no longer the driving force for Mattel’s management. Mattel did not see any economic benefit from its proactive stance, when competitors did not seem to suffer adverse consequences for not following suit. The final contributing factor to the code’s abandonment was a widely publicized series of product recalls which absorbed top management’s attention.
Keywords: top management and management incentives; Corporate Culture; and Indonesia; Thailand; Malaysia; manufacturing in China; Toy industry; Inc; Mattel; third party audits; corporate account- ability; Supply Chain Management; Outsourcing; Sweatshops; Voluntary codes of conduct